A Reflection on the Spanish Expresión Gráfica Arquitectónica at the Zaragoza Congress “Pingui Minerva” (diségno, 2021)
It is hard to choose a topic for intervening in a conference of this kind. It is a decision especially difficult if one wants to consider representing the general character of Spaniard assistants away from academic concerns and personal extravagances (as one may even say). Indeed, not everyone usually agrees about the great interest of these two aspects, although one is convinced of it. For such a reason, I have chosen a supposed ‘survey’ about the current studies and interests of the Spanish Expresión Gráfica Arquitectónica: a state of art’s synchronous cut. Of course, there is no such survey. However, a procedure has been used: a contributions’ analysis from the last congress of EGA. Such analysis allows access to a reflection similar to a survey and provides an approximate view of the whole. The last meeting of EGA titled El Patrimonio Gráfico. La Gráfica del Patrimonio (The Graphic Heritage. The Graphic of Heritage) was held virtually between the 4th and 6th of June 2020 in Zaragoza... [read more]